Enhanced Arterial Spin Labeling Magnetic Resonance Imaging of Cerebral Blood Flow of the Anterior and Posterior Circulations in Patients With Intracranial Atherosclerotic Stenosis - Yu, Hongwei; Li, Yangchen; Feng, Yibo; Zhang, Linwei; Yao, Zeshan; Liu, Zunjing; Gao, Wenwen; Chen, Yue; Xie, Sheng (Frontiers in Neuroscience, 2022)
Objectives This study analyzed differences in the mean cerebral blood flow (mCBF) and arterial transit time (ATT) of the anterior and posterior circulations between patients with intracranial atherosclerotic stenosis (ICAS) and control subjects. We also investigated the correlation between ATT and mCBF in the two groups, and evaluated whether the blood flow velocity of the extracranial carotid/vertebral arteries can influence mCBF. Methods A total of 32 patients with ICAS were prospectively enrolled at the Radiology Department of the China-Japan Friendship Hospital between November 2020 and September 2021. All patients had extensive arterial stenosis, with 17 having cerebral arterial stenosis in the anterior circulation and 15 in the posterior circulation. Thirty-two healthy subjects were enrolled as a control group. Enhanced arterial spin labeling (eASL) imaging was performed using a 3.0-T GE magnetic resonance imaging scanner, and all patients underwent carotid and vertebral Doppler ultrasound examinations. CereFlow software was used for post-processing of the eASL data, to obtain cerebral perfusion parameters such as mCBF and ATT. Independent samples t-tests were used to analyze and compare mCBF and ATT of the anterior circulation (frontal lobe, parietal lobe, and insula) and posterior circulation (occipital lobe, cerebellum) between the patient and control groups. The relationships of ATT and mCBF in the two groups were evaluated with Pearson’s correlation. The blood flow velocity of the extracranial internal carotid/vertebral arteries, including the peak systolic velocity (PSV), end diastolic velocity (EDV), mean PSV (mPSV), and mean EDV (mEDV), was compared between the control and study groups using t-tests. Multiple linear regression analysis was then applied to determine the factors associated with mCBF in the two groups. Results The mCBFs of the anterior and posterior circulations in the patient group were lower than those of the control group. The ATTs in the patient group were all significantly longer than those of the control group (p < 0.05). Except for the insula in the control group, significant correlations were found between ATT and mCBF in all other investigated locations in the two groups (p < 0.05). The blood flow velocity of the extracranial internal carotid/vertebral arteries differed significantly between the control and patient groups (p < 0.05). The multiple linear regression analysis revealed that in patients with ICAS, mPSV of the vertebral arteries and local ATT correlated with mCBF of the occipital lobes and the cerebellum, respectively (p < 0.05). In contrast, there was no significant correlation within the anterior circulation (frontal lobes, parietal lobes, and insula). Conclusion There was a significant relationship between ATT and mCBF in patients with ICAS. Extracranial blood flow may influence intracranial hemodynamics in the posterior circulation in patients with ICAS. The maintenance of extracranial blood flow is of great significance in the preservation of intracranial hemodynamics.